PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN HUMAN CAPITAL TERHADAP KINERJA KARYAWAN PADA PT BARKAH JAYA MANDIRI - Julia Retnowulan (Universitas Bina Sarana Informatika, 2017)
ABSTRACTThe era of globalization is characterized by increased competition, control over natural resources is not yet a guarantee of a company is able to win the competition, because this globalization era, followed by the rapid advances in innovation and creativity embodied in technological advancements. Human Resources (HR) is the key to win the competition in this era of globalization, for competent human resources to be able to produce a variety of creations and innovations that will lead to the value added at each business process. The purpose of this study was to determine and analyze the Transformational Leadership Style and Human Capital both partially and simultaneously the Employee Performance. This research was conducted by PT Barkah Jaya Mandiri against 55 employees and the collected data is processed by multiple regression. Penellitian results showed that transformational leadership, positive and significant impact on Employee Performance, Human Capital positive and significant impact on Employee Performance, Transformational Leadership and Human Capital simultaneously positive and significant influence on employee performance. Penellitian results showed that transformational leadership, positive and significant impact on Employee Performance, Human Capital positive and significant impact on Employee Performance, Transformational Leadership and Human Capital simultaneously positive and significant influence on employee performance.Keywords :Leadership Style, Human Capital, Employee Performance.